2007
DOI: 10.1159/000102679
|View full text |Cite
|
Sign up to set email alerts
|

The Origin and Evolution of Enamel Mineralization Genes

Abstract: Background/Aims: Enamel and enameloid were identified in early jawless vertebrates, about 500 million years ago (MYA). This suggests that enamel matrix proteins (EMPs) have at least the same age. We review the current data on the origin, evolution and relationships of enamel mineralization genes. Methods and Results: Three EMPs are secreted by ameloblasts during enamel formation: amelogenin (AMEL), ameloblastin (AMBN) and enamelin (ENAM). Recently, two new genes, amelotin (AMTN) and odontogenic ameloblast asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 225 publications
2
79
0
Order By: Relevance
“…The SCPP proteins include SIBLINGs (small integrin-binding ligand, N-linked glycoproteins) (18), which comprise osteopontin, DMP1, BSP, matrix extracellular phosphoglycoprotein, and DSPP. The SCPP family also includes the enamel matrix proteins: ODAM, AMTN, AMBN, and ENAM (19). In this study, we characterized the teeth of the Sox2-Cre-mediated Fam20C knock-out mice; the teeth of these mice showed severe defects in dentin, enamel, and cementum, which might be attributed to failures in the posttranslational phosphorylations of some secretory proteins in the SCPP family.…”
Section: Discussionmentioning
confidence: 99%
“…The SCPP proteins include SIBLINGs (small integrin-binding ligand, N-linked glycoproteins) (18), which comprise osteopontin, DMP1, BSP, matrix extracellular phosphoglycoprotein, and DSPP. The SCPP family also includes the enamel matrix proteins: ODAM, AMTN, AMBN, and ENAM (19). In this study, we characterized the teeth of the Sox2-Cre-mediated Fam20C knock-out mice; the teeth of these mice showed severe defects in dentin, enamel, and cementum, which might be attributed to failures in the posttranslational phosphorylations of some secretory proteins in the SCPP family.…”
Section: Discussionmentioning
confidence: 99%
“…We also showed that these KCOT-derived cells express major dental epithelial cell markers: AMELX, ENAM, AMBN, and AMTN. These major EMPs have been shown to have preferential expression in dental tissues, in particular the developing enamel producing ameloblasts (24). Prior studies have determined the localization of apoptosis and proliferation markers and an invasion-associated enzyme heparanase (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Seemingly, this short ODAM protein would be deficient in a secretory signal sequence and presumably would remain within the cell where it could have a more restrictive or differing functional role from that of the larger ODAM product. Notably, the gene encoding ODAM has been predicted to evolve from those specifying enamelin and other evolutionarily-derived dental components, for example, amelogenin and amelotin, where alternative splicing occurs (29)(30)(31); this phenomenon has been documented in over 60% of human and mouse genes (32).…”
Section: Discussionmentioning
confidence: 99%